2020
DOI: 10.1136/rmdopen-2019-001085
|View full text |Cite
|
Sign up to set email alerts
|

Measuring ACPA in the general population or primary care: is it useful?

Abstract: Rheumatoid arthritis (RA) is associated with a significant disease burden and high costs for society. Because the disease has identifiable preclinical stages, screening and prevention have become a possibility in RA. Anticitrullinated peptide antibodies (ACPAs) are arguably the most likely candidate biomarker to screen for RA. This paper reviews the evidence for the use of ACPAs as a screening test in the broader general population, to identify individuals at high risk of subsequent onset of RA. We will review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The overall cohort tested over 9000 potential participants since 2008, while about >750 were included being ACPA+in line with reported prevalence of ACPA-positivity. 45 The populations and models developed for ACPA+arthralgia 22 46 are therefore not directly transferable to cohort of patients with CSA (as defined by EULAR taskforce 42 47 48 ), or in first degree relatives of patients with IA, 49–51 which are the other main characteristics used for selecting at risk individuals. In addition, progression rate in these different groups are different and if 32% for IA in our cohort, progression to RA was only observed following from the development of IA in less than 25% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall cohort tested over 9000 potential participants since 2008, while about >750 were included being ACPA+in line with reported prevalence of ACPA-positivity. 45 The populations and models developed for ACPA+arthralgia 22 46 are therefore not directly transferable to cohort of patients with CSA (as defined by EULAR taskforce 42 47 48 ), or in first degree relatives of patients with IA, 49–51 which are the other main characteristics used for selecting at risk individuals. In addition, progression rate in these different groups are different and if 32% for IA in our cohort, progression to RA was only observed following from the development of IA in less than 25% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…As criteria are needed to define an at-risk population and to balance the specificity of the recruitment with the number of cases needed to develop models. The overall cohort tested over 9000 potential participants since 2008, while about >750 were included being ACPA+in line with reported prevalence of ACPA-positivity 45. The populations and models developed for ACPA+arthralgia22 46 are therefore not directly transferable to cohort of patients with CSA (as defined by EULAR taskforce42 47 48), or in first degree relatives of patients with IA,49–51 which are the other main characteristics used for selecting at risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The positive predictive value (PPV) of ACPA tests, which demonstrates the likelihood of an individual with a positive test to have or develop a condition, varies in different studied populations – from 9% in the general population to 55% when both environmental and genetic risk factors are present, 52% in clinically suspect arthralgia (CSA) and >80% in undifferentiated arthritis patients [ 129 ]. Multivariable analysis in one study showed ACPA-positivity to be an independent risk factor for RA development in individuals with CSA (hazard ratio (HR) = 5.1; 2.0–13.2) and to have a 50–67% PPV (RF-negative/RF-positive) for RA development within 2 years [ 125 ] .…”
Section: Clinical Relevance Of Autoantibodies In Ramentioning
confidence: 99%
“…The detection of circulating antibody titers against citrullinated (cyclic) peptides (CCP), e.g. anti-citrullinated peptide antibodies (ACPA) is used today for differential diagnosis, therapeutic follow-up and prognosis of patients with various forms of arthritis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%